Chapter 4 Evaluating electoral management performance the PROSeS framework - James, Toby S. (Routledge Studies in Elections, Democracy and Autocracy, 2020)
After a review of the rival approaches that are used to evaluate public sector performance in general, five dimensions of EMB performance are set out which are argued to be crucial for achieving democratic ideals in an electoral democracy. The aim is to set out these dimensions, and the sources of data that can be used by researchers to assess whether they are achieved. The UK and Canada are then assessed against the framework so that the utility of the model becomes clear. The concepts and framework also act as founding principles for the remainder of the book.